PENGGUNAAN APLIKASI WHATSAPP DAN GOOGLE CLASSROOM PADA PEMBELAJARAN MATEMATIKA DI MASA PANDEMI COVID-19 - Arsyil Waritsman; Dian Untari (Balai Diklat Keagamaan Bandung, 2022)
The purpose of this study was to describe (1) the process of mathematics learning using Whatsapp and Google classroom and (2) the constraints experienced by teachers and students regarding the use of these two applications in Mathematics learning. This research is a descriptive study with a qualitative approach. The data collection technique used is interviews, observation, and documentation. The research subjects were a mathematics teacher and two students. The results showed that (1) Mathematics learning process was running smoothly where Whatsapp was used for core learning activities and Google classroom was used to access material and practice questions; (2) The obstacles faced by teachers and students are more directed at the less stable internet network. In general, the use of Whatsapp and Google classroom in learning Mathematics runs quite well. Keywords: Learning; Mathematics; Application; Covid-19